Ten Years of Data Verification: The Society of Thoracic Surgeons Congenital Heart Surgery Database Audits. Issue 4 (July 2019) - Overman, David M.; Jacobs, Marshall L.; O'Brien, James E.; Kumar, S. Ram; Mayer, John E.; Ebel, Angela; Clarke, David R.; Jacobs, Jeffrey P.
Background: The completeness and accuracy of data contained within clinical databases and registries is critical to the reliability of reports emanating from these platforms. Therefore, vigorous data verification processes are a core competency of any mature database or registry. The Society of Thoracic Surgeons Congenital Heart Surgery Database (STS CHSD) has conducted audits of participant data for just over ten years. This report documents the validity of data elements within the STS CHSD. Methods: We review the various elements of a robust audit process, detail the STS CHSD audit methodology, and report completeness and agreement rates for all adjudicated fields in the most recently completed audit. Results: The rate of completeness for general data elements was 97.6% and the rate of agreement was 97.4%. The rate of completeness for variables in the mortality review was 100% and the rate of agreement was 99.3%. Conclusions: The STS CHSD audit is a highly structured and reproducible process. The most recently completed audit documents a very high level of completeness and accuracy of data variables, particularly those most germane to outcomes measurement.